Innovating governance Building resilience against the COVID-19 pandemic and other risks. (Philippine Institute for Development Studies (PIDS), 2020)
The coronavirus disease (2019) pandemic is by far the most challenging public health crisis the world has faced in a century. Its effects have now extended beyond healthcare systems to entire economies. During unsettling times like this, the role of evidence-based research cannot be overemphasized.